Effects of Aeration System to Water Quality (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
A study of effect of aeration system to water quality in Sungai Kangka, Politeknik Kuching Sarawak has been conducted to identify the suitable aeration system can be applied in Sungai Kangka as alternative method to reduce pollution level in Sungai Kangka to a safe level for recreational purposes. Through this aim, the main objective of this study is to provide technical data of water quality in Sungai Kangka after been conducted in several aeration test. The parameters that have been evaluated are dissolved oxygen (DO) which contribute to the healthy growth of organisms in river and surrounding, the aerator speed which is rotation per minute (RPM) and the dimensions of the bubble stone aerator (mm). The water sample was taken on two conditions which are the continuously flowing and stagnant point in river stream. Dissolved oxygen levels in flowing river stream were set as benchmarks and the dissolved oxygen level at the stagnant point was enhanced through aeration system which is impeller and fan aeration system and bubble aeration system. Water sampling initially measured in two sampling points, which is 5.31 mg/L and 4.61 mg/L respectively before aeration process conducted on stagnant point sampling. The data obtained shows that impeller and fan aeration system suitable for river stream which ensures the river stream to continuously flowing and reducing stagnant point in river. Although, the increase the DO level in bubble aeration system has higher percentage compared to fan aeration system, it’s suitable to use in pond, water treatment plant and sewerage treatment plant.